2018
DOI: 10.1111/jvh.13017
|View full text |Cite
|
Sign up to set email alerts
|

Increased diagnosis and treatment of hepatitis C in prison by universal offer of testing and use of telemedicine

Abstract: Summary With recent advances in antiviral therapy, there is an opportunity to eliminate hepatitis C virus (HCV) from the UK population. HCV is common in incarcerated individuals, with previous estimates suggesting ~7% of the UK prison population is anti‐HCV antibody positive. Increasing diagnosis and treatment of HCV in prison is a priority in seeking to eliminate transmission in the general population. Thus the study aimed to assess the impact implementation of: (a) A universal offer of blood borne virus test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
80
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 57 publications
(86 citation statements)
references
References 27 publications
4
80
2
Order By: Relevance
“…In this review, we have demonstrated a high percentage of initiation of HCV treatment (71%) following diagnosis of active HCV within the NEE prisons using a treatment pathway that incorporates nurse‐led in‐reach and consultant delivered telemedicine clinics. This represents a large increase when compared with previous treatment data in our prisons (14%) and data reported elsewhere . However, approximately 30% of HCV viraemic individuals still do not commence antiviral treatment, mainly due to short sentences.…”
Section: Discussioncontrasting
confidence: 47%
See 4 more Smart Citations
“…In this review, we have demonstrated a high percentage of initiation of HCV treatment (71%) following diagnosis of active HCV within the NEE prisons using a treatment pathway that incorporates nurse‐led in‐reach and consultant delivered telemedicine clinics. This represents a large increase when compared with previous treatment data in our prisons (14%) and data reported elsewhere . However, approximately 30% of HCV viraemic individuals still do not commence antiviral treatment, mainly due to short sentences.…”
Section: Discussioncontrasting
confidence: 47%
“…Following a pilot in HMP Durham and HMP Northumberland beginning in March 2016, all seven NEE prisons had fully operational UOBBVT and HCV treatment pathways by April 2017. All BBVT was conducted using dry blood spot testing (DBST) and tested for HCV, HBV and HIV as previously described . Individuals in receipt of a positive HCV RNA result on the DBST were reviewed in Prison Healthcare and had a venous sample taken to confirm active infection using HCV RNA along with other pre‐treatment blood tests, such as genotype.…”
Section: Methodssupporting
confidence: 46%
See 3 more Smart Citations